2020
DOI: 10.31234/osf.io/fdvh6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visible and invisible displacement with dynamic visual occlusion in bottlenose dolphins (Tursiops spp)

Abstract: Anticipating the location of a temporarily obscured target—what Piaget (the construction of reality in the child. Basic Books, New York, 1954) called ‘‘objectpermanence’’—is a critical skill, especially in hunters of mobile prey. Previous research with bottlenose dolphins found they could predict the location of a target that had been visibly displaced into an opaque container, but not one that was first placed in an opaque container and then invisibly displaced to another container. We tested whether, by alte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…However, as has been cautioned by a number of researchers, low-level associative explanations must be controlled for in these studies (e.g., Andrews, 2017;Heyes, 2014). Finally, experimental procedures that harness ecological validity have been more successful in demonstrating advanced aspects of ToM and complex social behaviors than the more artificial procedures in primates and dolphins (e.g., Buttelmann, Buttelmann, Carpenter, Call, & Tomasello, 2017;Hare, 2001;Johnson et al, 2015;Kaminski et al, 2008;Kano et al, 2017;Krupenye et al, 2016). For example, Johnson et al (2015) successfully modified the traditional container testing paradigm for invisible displacement with dolphins by adapting an occlusion method and gaze direction measure successfully utilized with human infants, which evidences the need for an adaptable comparative approach (Onishi & Baillergeon, 2005;Surian, Caldi, & Sperber, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, as has been cautioned by a number of researchers, low-level associative explanations must be controlled for in these studies (e.g., Andrews, 2017;Heyes, 2014). Finally, experimental procedures that harness ecological validity have been more successful in demonstrating advanced aspects of ToM and complex social behaviors than the more artificial procedures in primates and dolphins (e.g., Buttelmann, Buttelmann, Carpenter, Call, & Tomasello, 2017;Hare, 2001;Johnson et al, 2015;Kaminski et al, 2008;Kano et al, 2017;Krupenye et al, 2016). For example, Johnson et al (2015) successfully modified the traditional container testing paradigm for invisible displacement with dolphins by adapting an occlusion method and gaze direction measure successfully utilized with human infants, which evidences the need for an adaptable comparative approach (Onishi & Baillergeon, 2005;Surian, Caldi, & Sperber, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, experimental procedures that harness ecological validity have been more successful in demonstrating advanced aspects of ToM and complex social behaviors than the more artificial procedures in primates and dolphins (e.g., Buttelmann, Buttelmann, Carpenter, Call, & Tomasello, 2017;Hare, 2001;Johnson et al, 2015;Kaminski et al, 2008;Kano et al, 2017;Krupenye et al, 2016). For example, Johnson et al (2015) successfully modified the traditional container testing paradigm for invisible displacement with dolphins by adapting an occlusion method and gaze direction measure successfully utilized with human infants, which evidences the need for an adaptable comparative approach (Onishi & Baillergeon, 2005;Surian, Caldi, & Sperber, 2007). The training and testing protocols used by Brosnan and her colleagues in their investigations of cooperation, decision making, and equity using variations of the "Stag Hunt" game or the Assurance game are excellent examples of ecologically valid methodologies that require limited training and enable cross-species comparisons (Brosnan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our dependent measure was whether the dolphin turned its head to the right or left during these 2 s in anticipation of the target reappearing on one side or the other of the occluder. Previous work with the same animals involving the occlusion of dynamic, 2-D images (judging visible and invisible displacement; see Johnson, Sullivan, Buck, Trexel, & Scarpuzzi, 2015) showed that they would often turn to look in the direction they expected an object to reappear. In rare cases, dolphins looked in more than one direction; for all of these cases, we counted the first head turn.…”
Section: Experiments 1 Methodsmentioning
confidence: 96%